2018
DOI: 10.1177/1043659618777051
|View full text |Cite
|
Sign up to set email alerts
|

Paper Spirits and Flower Sacrifices: Hmong Shamans in the 21st Century

Abstract: Nurses' awareness that the availability of biomedicine does not preclude the continuing or recurring utilization of traditional healers can facilitate understanding of culturally defined health care needs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 10 publications
(13 reference statements)
0
5
0
Order By: Relevance
“…Many studies have indicated the use of traditional medicine and modern medicine [2][3][4]. Use of spiritual healing in sickness is documented in America and Asia [26][27][28]. During the epilepsy care seeking process in this study, many patients use different drugs for treating the same episode.…”
Section: Discussionmentioning
confidence: 84%
“…Many studies have indicated the use of traditional medicine and modern medicine [2][3][4]. Use of spiritual healing in sickness is documented in America and Asia [26][27][28]. During the epilepsy care seeking process in this study, many patients use different drugs for treating the same episode.…”
Section: Discussionmentioning
confidence: 84%
“…In the context of local Miao healing ceremonies, the role of the shaman assumes a paramount significance. The shaman functions as a conduit, facilitating communication between descendants and ancestral spirits and, thus, serving as an intermediary in the ex-change of desires and intentions between the living and the departed (Plotnikoff et al 2002;Helsel 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In addition to their abilities to "discern life and death, foresee years and months like deities", they engage in ritualistic elements such as song and dance, overseeing activities encompassing sacrificial rites, divination, and supplications. These roles extend to dispelling malevolent forces, invoking blessings, averting disasters, predicting abundance or scarcity, and providing medical treatment, constituting integral facets of their customary functions (Helsel 2019). For Miao healers, the term "wū (巫)" (literally, shaman/spirit healer) serves not merely as a conduit for spiritual therapy but also as a diagnostic instrument.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations